The Effect of 3D Printing Metal Materials on Osteoporosis Treatment. (18th June 2021) - Wang, Bing; Feng, Chuwen; Pan, Jianyu; Zhou, Shuoyan; Sun, Zhongren; Shao, Yuming; Qu, Yuanyuan; Bao, Shengyong; Li, Yang; Yang, Tiansong
Abstract : 3D printing has been in use for a long time and has continued to contribute to breakthroughs in the fields of clinical, physical, and rehabilitation medicine. In order to evaluate the role of 3D printing technology in treating spinal disorders, this paper presents a systematic review of the relevant literature. 3D printing is described in terms of its adjunctive function in various stages of spinal surgery and assistance in osteoporosis treatment. A review of metal 3D printed materials and applications of the technology is also provided.